Women With Amenorrhea and Men With Menstruation: The Qualitative Experiences of People With Disorders of Sex Development in Nigeria. Issue 1 (February 2020) - Sani, Abdurrahman Muhammad; Arif, Ismi Ismail; Arshad, Mohd Mursyid; Mungadi, Ismaila Arzika; Soh, Kim Geok; Soh, Kim Lam
ABSTRACT: Background: Disorders of sex development (DSD) affect the quality of life of people who live with this condition. In developing countries, diagnoses of DSD are associated with a delay in presentation until the patients developed ambiguous physical traits and features. Purpose: This study explores the menstrual experiences of people with DSD and sex reassignment in Nigeria. Methods: A qualitative approach with a phenomenological study design was employed in this study to explore and describe the experiences of people with DSD at the Usmanu Danfodiyo University Teaching Hospital in Sokoto, Nigeria. The data were collected using face-to-face interviews, transcribed verbatim, and analyzed using NVivo software. Results: The findings show that the participants experienced menstrual problems: men with menstruation and women with amenorrhea. The female participants generally described amenorrhea as a disappointment and linked menstruation with womanhood. Amenorrhea evinced both emotional and psychological effects. However, some of the female participants considered amenorrhea in a positive light and were happy with their lives without menstruation. The menstrual experiences of male participants included menarche, lower abdominal pain, regular monthly bleeding, and ovulation. The male participants described menstruation as a disaster in their lives and a source of anxiety, suicidal ideation, and depression. Menstruation negatively affected their psychosocial well-being. Conclusions: The menstrual experience of individuals with DSD negatively affects their quality of life. The women with DSD in this study showed a generally poor knowledge of menarche, menstruation, and puberty, indicating that their parents had ignored the initial symptoms of DSD. DSD were only recognized at puberty because of the development of ambiguous physical traits and of the onset of menstruation in men and the confirmation of amenorrhea in women.